(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
Law No. 12,244, of May 24, 2010, establishes the mandatory implementation of school libraries in Brazil. From this perspective, this article aims to identify which actions were taken to implement Law No. 12,244/2010 in the public educational network in the municipality of Joaquim Gomes. The research is characterized as a descriptive type with a qualitative approach, data were collected via questionnaire in July 2023 and the analysis was by categories. From the research data, it was found that the municipality is far from complying with the law, of the 15 schools in the municipality, 6 have libraries, but none with a professional librarian. Therefore, it is expected that this research will contribute to the recognition, by the municipal secretary and school management, of the need to comply with the legislation. And with that recognizing the importance of the library in school life, thus promoting full access to knowledge.